Department Chairs' Trends and Issues: An 11-Year Study - Robert E. Cipriano Dr. (Academic Chairpersons Conference Proceedings, 2018)
This interactive workshop will present, discuss and analyze data comparing and contrasting responses of more than 2,200 department chairs from 2007 - 2017. Trends that have emerged over the 11-years of this study will be synthesized in order for the attendees to gain insight into the myriad ways that the role of the chair has changed, and offer a look into the future.
Keywords: department chair; characteristics of chair; challenges chairs have; satisfaction of serving as chair; why chairs remain/why chairs leave.